The Teacher: Solid Presence and Fine Sensitivity - Raffaele Beretta Piccoli (University of Bologna, 2022)
The article begins with an analysis of the learning process, described as a transition from a condition of "not knowing (doing)" to a condition of "knowing (doing) something more". Referring to John Dewey's theory, it underlines the need, on the part of the teacher, to understand the specific condition of the learner, which is closely related to the uncomfortable posture of learning, in order to make possible a truly meaningful pathway. To foster this experience, the author proposes, in conclusion, two thoughts: the first is focused on the competence to proactively and interactively regulate the lessons, the second on a "principle of excess" which constantly places the teacher in the position of "giving".